Efektivitas Biaya Penggunaan Omeprazole Dan Ranitidin Pada Pasien Gastritis - Sunarti, Sunarti; Sholihah, Nur Aminatus; Oetari, Oetari (Universitas Harapan Bangsa Purwokerto, 2019)
ABSTRACT Gastritis is an inflammation of the gastric mucosa caused by various factors such as Helicobacter pylori infection which can occure acute or chronic. The use of ranitidine therapy in gastritis patients is greater than omeprazole. The aim of the study was to analyze the cost-effectiveness of treating inpatient gastritis patients using omeprazole or ranitidine. The study was an observational cross-sectional method according to the hospital's perspective using secondary data in January-December 2016 period regarding the treatment of 65 BPJS class-III gastritis patients.The data includes demographic data, length of stay and total costs. A total of 32 patients class III BPJS use omeprazole and 33 patients use ranitidine. Patients age ranged from 17-65 years. Statistical used independent t-test. The results showed female (72.31%), aged 17-38 (60%) and length of stay 3-4 days (56.9%). Average total cost of omeprazole therapy Rp. 544,802.59 and ranitidine Rp. 557,563.12, with probability 0,696 > 0,05, so the result was not significantly different. Omeprazole therapy was more effective than ranitidine with percent of effectiveness 59,38% and 51,41%. ACER value of omeprazole therapy Rp. 9.234,06/1% recovery was more less than ranitidine Rp. 10.932,61/1% recovery. So omeprazole more cost-effective than ranitidine Keyword : Cost Effectiveness Analysis, gastritis, omeprazole, ranitidine